GLOBALIZATION OF MUSLIM CONSCIOUSNESS IN THE CAUCASUS: SLAMIC CALL AND JIHAD - KURBANOV, Ruslan (CENTRAL ASIA AND THE CAUCASUS, 2006)
Today most researchers of North Caucasian religious-political reality are viewing the role of the international factor in the region’s Islamic revival exclusively from the narrow perspective of its financing by the worldwide terrorist international aimed at destabilizing the situation in the Caucasus. However, the circumstances that have brought the problems relating to the North Caucasian Islamic revival to the international level are much more complicated and multifaceted. Let us begin with the fact that for many centuries, the interpretation and practice of Islam established in the Caucasus developed according to their own scenarios and were very different from that customary throughout the Caliphate as a whole. First of all, the Muslims of the Caucasus were very isolated from the external Muslim world. Due to the region’s remoteness from the political centers of the Caliphate, as well as the inaccessibility of the interior regions of the Caucasus, internal caliphate social, political, military, cultural, and other transformations reached it in the form of weak echoes. Second, because of the incredible internal strength and tenacity of the local traditional spiritual and ritual-legal cultures, the interpretation and practice of Islam in the Caucasus were strongly influenced by them. For centuries, the Islamic religion had to reconcile itself to living next door to ineradicable paganism in everyday life, the adapts, the everyday behavior of the mountaindwellers, and their consciousness. This caused the ritual side of Islam to become extremely deformed in the region, while the legal space of the Caucasus was divided between the traditional adat and the Shari‘a, a situation that was inconceivable for classical Islam. This last factor played an enormous role in the victory of czarist, and then Soviet Russia in the Caucasian theater of war. It was precisely due to the heterogeneity, lack of integrity, and fragmentariness of the Islamic consciousness, as well as the interruption of the legal space and the uneven “filling” of the mountain society with Islamic power that the czarist and Soviet authorities were able to split Caucasian society and implement their own political and legal projects in the region. After the czarist authorities spent decades quietly stifling Islamic political-legal practice and intellectual thought, and after virulent destruction of the latter by Soviet power, the authorities were taken completely by surprise when Islam suddenly erupted in a burst of activity in all areas of life in the region, leading to a so-called Islamic revival. This phenomenon is extremely complicated and multifaceted, and it is precisely this explosive awakening of Islam in the Caucasus that interests us as we take a look at Islamic globalism in the region’s Muslim consciousness.